Integrating urban development and ecological sustainability: a study on land surface temperature and urban heat island effect in a Karst River Basin - Wu, Yangyang; Wu, Haobiao; Li, Siliang; Wu, Liqing; Guo, Chunzi; Zhang, Zhonghua; Fan, Ruixue; Yang, Xiaodong; Zhou, Guanghong; Yang, Jinli; Yuan, Panli; Luo, Guangjie (Frontiers in Built Environment, 2024)
The Chishui River Basin, a vital waterway in Southwest China, has experienced rapid urbanization, leading to significant ecological and environmental changes, among which the urban heat island (UHI) effect is particularly pronounced. The UHI effect not only affects the quality of life for residents but also influences urban energy consumption and climate change, underscoring the need for in-depth study of its spatial distribution and contributing factors. The unique karst topography of the region further complicates UHI research, necessitating an investigation that can inform urban planning and sustainable development strategies. This study leveraged Landsat 8 TIRS satellite remote sensing imagery to examine the land surface temperature (LST) and UHI effect in the Chishui River Basin during the summers of 2016 and 2021. Employing the Mono-window Algorithm (MWA), the research quantitatively inverted the LST and analyzed its spatial distribution and the spatiotemporal characteristics of the surface urban heat island (SUHI) effect. The findings indicated a notable increase in average summer temperatures between the 2 years, with a 1.67°C rise from 2016 to 2021. Despite this increase, there was an observed reduction in the extent of SUHI areas, suggesting potential mitigation efforts. Additionally, the study revealed that karst regions were more susceptible to forming “abnormal” heat islands due to their distinct geomorphological features. The implications of this research are critical for urban development planning and the pursuit of sustainable urbanization in the Chishui River Basin. By understanding the thermal dynamics and their relationship with urbanization and karst landscapes, policymakers and urban planners can devise strategies to minimize the adverse effects of SUHI while promoting ecological balance and environmental health. Future research should extend the temporal analysis, employ higher resolution data, compare findings with other regions, and provide a detailed examination of mitigation efforts to enhance the robustness and applicability of the conclusions, provide stronger scientific evidence for the ecological sustainability of the Chishui River Basin.